The Battle of Advantage between Stealing and Decrypting the German Naval Enigma Key in the Battle of the Atlantic (1940-1941) - Liang, Hangyu (Transactions on Social Science, Education and Humanities Research, 2024)
In the early years of World War II, German Navy used Enigma to encode messages and prevent their intelligence by Allies. This work considers advantages of stealing and technically decrypting the German Naval Enigma key during the Battle of Atlantic from 1940-41; while Allies had already succeeded in decrypting the German Army Enigma prior to the war. The complexities of Naval Enigma introduced new challenges. Yet British codebreakers persisted with technological decryption — an approach they adopted following their earlier successes. However, details embedded within Naval Enigma plus changes implemented by Germans stood as obstacles against their progress. Solving the encryption required more than what had been previously done. This led them to take an unconventional path: stealing materials related to Enigma. This decision was resource-intensive but it paid off quickly in yielding results that were more practical and morally justifiable than pure decryption efforts made until then. The successful thefts like that which took place during the Lofoten Islands raid and in May 1941 when German ships were captured provided critical Enigma keys and quickened decryption, allowing Allies to obtain valuable intelligence, reroute convoys, and better address the U-boat threat. The work concludes that from a utilitarian perspective stealing Enigma materials was morally justified because it minimized Allied casualties. It also notes that the non-malicious intentions behind theft conformed to deontological principles, underscoring the ethical standing of British actions vis-a-vis Germans'. Ultimately, the British strategy of technological decryption combined with thefts led decisively to turning the tide against Nazis during Battle of Atlantic: hence this paper investigates whether we might perhaps say they were acting ethically (even if illegally) by stealing Enigma-related material.